IL-13 Alleviates Cardiomyocyte Apoptosis by Improving Fatty Acid Oxidation in Mitochondria - Guo, Xiaoyu; Hong, Ting; Zhang, Shen; Wei, Yazhong; Jin, Haizhen; Miao, Qing; Wang, Kai; Zhou, Miao; Wang, Chong; He, Bin (Frontiers in Cell and Developmental Biology, 2021)
Sepsis-induced cardiac injury (SIC) is one of the most common complications in the ICU with high morbidity and mortality. Mitochondrial dysfunction is one of the main reasons for SIC, and IL-13 is a master regulator of mitochondria biogenesis. The aim of the present study was to investigate the role of IL-13 in SIC and explore the underlying mechanism. It was found that ROS production and apoptosis were significantly increased in LPS-stimulated primary cardiomyocytes, which was accompanied with obvious mitochondria dysfunction. The results of RNA-seq, mitochondrial membrane potential, fatty acid uptake and oxidation rate suggested that treatment with IL-13 could restore the function and morphology of mitochondria, indicating that it played an important role in protecting septic cardiomyocytes. These findings demonstrated that IL-13 alleviated sepsis-induced cardiac inflammation and apoptosis by improving mitochondrial fatty acid uptake and oxidation, suggesting that IL-13 may prove to be a potential promising target for SIC treatment.